Synthesis of fish gelatin nanoparticles and their application for the drug delivery based on response surface methodology - Subara, Deni; Jaswir, Irwandi; Al-Khatib, Ma An Fahmi Rashid; Ibrahim Ali, Noorbatcha (Institute of Physics Publishing, 2018)
Fish gelatin nanoparticle is produced using Tilapia fish skin for the first time by the two-step desolvation method. Fish gelatin is chosen for producing gelatin nanoparticles because no experiment have been done in using fish gelatin and to counter the problem associated with the use of mammalian gelatin, such as bovine spongiform encephalopathy disease. The effects of several factors on the particle size such as pH, acetone concentration, glutaraldehyde volume, stirring speed and stirring time are evaluated. Optimum conditions for the formation of gelatin nanoparticles are obtained using response surface method. Fish gelatin nanoparticles with optimum size of 198.46 ± 6.1 nm can be produced using pH of 2.45, acetone percentage of 16% (vol%), glutaraldehyde 400 μ, stirring speed of 600 rpm, and stirring time for 6 h. The thermogram and molecular interaction of fish gelatin and fish gelatin nanoparticles are characterized using DSC and FTIR. In vitro drug release kinetic is examined using 5-fluorouracil as the model drug. The entrapment efficiency of 5-fluouracil as model drug is determined to be 40%. Fish gelatin could be used as a good alternative drug carrier for mammalian gelatin.